KONSEP FEMINISME ISLAM DI DALAM FILEM KETIKA CINTA BERTASBIH - Yusof, Abdullah; Abd Rahim, Rahimin Affandi; Abdul Kadir, Nor Adina; Md Dahlal, Nor Hayati (Journal of Al-Tamaddun, 2010)
The application of message and social issues through films is within the framework of educating and constructing the mindset of the society. This article will focus on the elements of feminism in Islamic movie, Ketika Cinta Bertasbih directed by Chaerul Umam. It contains a number of analyses. Firstly, the introduction to what and how the concept of feminism developed in the society. Second, the responses of Muslim scholars toward the concept of feminism. Third, the uniqueness of the film Ketika Cinta Bertasbih as the focus of the study. Fourth, analysis of the feminism theme in the film and fifth, the conclusion. This film contains the element of literature through the use of certain words in conveying a message. Feminism in the society, whether in the Malay society or other communities is still relevant to be discussed by academicians or in the creative writing circles including film due to the difference in human interests between men and women in aspects such as politics, economy, social and culture. Apart from that, the genre of Islamic film proves the beauty of Islam itself, which is perfect, complementing and solves the issues of life.